BIOLOGICALLY ACTIVE POLYBROMINATED INDOLES IN THE RED ALGA LAURENCIA SIMILIS FROM THE COASTAL WATERS OF SABAH (RHODOMELACEAE, CERAMIALES) - Charles Santhanaraju, Vairappan; May Yen, Ang; Cheng Yi, Ong; Siew Moi, Phang (Malaysian Journal of Science, 2004)
The red alga Laurencia similis Nam et Saito collected from six locations in coastal waters of Sabah, contained two polybrominated indoles in high quantities, 2,3,5,6-tetrabromoindole (1) and 1-methyl-2,3,5,6-tetrabromoindole (2). Structures of these compounds were determined based on their spectroscopic data and other physical characteristics. Total percentage of these compounds in samples analyzed were in this order; Tg Aru (58%) > Sepanggar Island (47%) > Kudat (41%) > Mantanani Island (32%) > Lankayan Island (28%) > Sipadan Island (26%). Isolated compounds showed a wide spectrum of activities against human pathogenic yeast, environmental bacteria and fungus. Compound 1, 2, 3, 5, 6-tetrabromoindole, in particular showed significant activity against the tested microbes. Potencies of the brominated metabolites were also compared against 13 types of commercially available antibiotic sensitivity test bio-discs.